IMPLEMENTATION OF ADMINISTRATIVE SANCTIONS FOR RESTAURANT TAXES AS REGIONAL ORIGINAL INCOME - Elza Suryawan Martioso; Indriati Amarini; Ika Ariani Kartini (UMPurwokerto Law Review, 2020)
Regional Original Income is revenue that is obtained by the regional government for the implementation of government and services to the community. One source of local revenue is the restaurant tax. However, often the tax is not optimal because it is considered to result in high economic costs and less support for business or investment including restaurant tax. The purpose of this study was to determine the provisions of administrative sanctions against restaurant tax offenders. This research uses normative juridical research with data in the form of books, journals, research results, and related laws and regulations. The results showed that restaurant tax as a source of local revenue was regulated by Regional Regulation. Provisions on administrative sanctions are regulated in regional regulations by adjusting the conditions in each area. Local regulations on restaurant taxes should contain clear and strict sanctions so they can be effective.Keywords: administrative sanctions, restaurant tax, local own income